Impact of low temperature on ex situ nitritation/in situ denitritation in field pilot-scale landfill for postclosure care of leachate treatment and gas content. (15th July 2021) - Yang, Nuan; Tao, Yong; Wang, Xiaomei; Zhan, Guoqiang; He, Xiaohong; Zhang, Lixia; Li, Wei; Ding, Yong; Li, Daping
Graphical abstract: Highlights: Low temperature of below 15 °C was evaluated in the closed landfill. Efficient and effective postclosure care of leachate and gas was achieved. Oxidized nitrogen was degraded during postclosure care of landfill leachate. TON loading rate was below a threshold value of methanogenesis inhibition. Low methane content was observed during in situ denitritation. Abstract: Leachates and landfill gas (LFG) are the major problems for closed landfills (CL) and cause significant threats to receiving waterbody and ambient air quality. In this study, a field pilot-scale CL with ex situ nitritation/in situ denitritation process was constructed and operated continuously under wide temperature variations. The effect of low temperature on leachate treatment, and LFG content was studied. Results showed that the combined process can efficiently remove nitrogen and organic matters from leachate, and change LFG content under low-temperature condition. In the ex situ nitritaion, maximum removal efficiencies of ammonia and chemical oxygen demand (COD) were over 99% and 85%, respectively. The loading rate of nitrogen and COD reached 0.5 kg N m −3 d −1 and 0.7 kg COD m −3 d −1, respectively. The inhibitions of free ammonia (FA) and free nitrous acid (FNA), and low temperature were the key factors affecting nitritation. With recirculating nitrified leachate, total oxidized nitrogen (TON) was completely reduced, and the refuse decomposition was accelerated. Denitritation was the main reaction responsible in the CL. Additionally, methane content was observed lowly at non-inhibitory TON loading rate of 5.8 ± 3.7 g N ton −1 TS d −1 . This decrease was not caused by the increased of TON loading, but a carbon source competition by denitrificans. The estimated COD consumption and methane reduction were 55.0 kg d −1 by TON reduction, and 20 m 3 d −1, respectively. Hence, this study served a potential strategy for postclosure care of landfills under low temperature variation.